Participatory gender-sensitive approaches for addressing key climate change- related research issues: Evidence from Bangladesh, Ghana, and Uganda - Chaudhury M; Kristjanson, Patricia M.; Kyagazze F; Naab, Jesse B.; Neelormi S (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
Getting a better understanding of how climate variability affects rural men and women differently, and in different regions, is challenging. Since their ability to respond to change and take action that will make them more resilient and able to adapt to a changing climate (alongside all the other social and economic change they are dealing with) differs, we need to focus more research efforts on enhancing this understanding and linking this knowledge with actions aimed at enhancing livelihoods and food security. We examine how well existing participatory gender-sensitive research approaches address some key climate change-related research issues that CCAFS has prioritized. Bringing together gender experts and experienced agricultural research teams from Bangladesh, Ghana, and Uganda, multiple methods were tested in the field, and refined through the lessons learned, to help inform future action research and development efforts towards enhancing communities’ and individuals’ (particularly women’s) access to, and use of, information and knowledge to help them adapt to climate variability through more resilient livelihoods and agro-ecosystems.